SISTEM INFORMASI PENJUALAN TOKO RAJA BUNGA ANGGREK DESA PAKOPEN DENGAN MENGGUNAKAN METODE WATERFALL - Erika Ifalinda; Abdul Rohman (Universitas Ngudi Waluyo, 2023)
Utilization of information systems in today's business world, it is very important to support the creation of digital or online activities or transactions, especially in sales information systems, Raja Bunga Orchid is a store engaged in selling Orchids and various care products and equipment. using social media facilities, so that the recording of sales transactions is still manual, and errors often occur. There is no web-based sales information system at the Raja Bunga Anggrek store. The system development method used by the researcher is using the waterfall method in building an information system for the sale of the King of Orchids. The waterfall method is one method that is systematic or sequential. The data analysis method uses qualitative methods and the test method is using qualitative methods to obtain the final data. From the results of testing the sales system, it was found that a percentage of 86% was taken from usability and functionality tests, which means that the system created can be used to meet the author's goals which can be included in the